El mejoramiento de frijol en Guatemala. Introduccion de programa de mejoramiento ICTA. El equipo, sitios, objetivos, facilidades disponibles, aspectos claves en su organizacion y manejo - Masaya S, P (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
Overall objectives of the Bean Improvement Program of the Guatemalan Instituto de Ciencia y Tecnologia Agricola (ICTA) are to (1) generate reliable, easily adaptable, low-cost technology and (2) promote technology transfer and seed production. The breeding strategy makes use of the genetic variability found in native or local materials and in those included in CIAT's germplasm bank. The impact of the development of new var. on production is considered. Stages involved in the process of technology generation and transfer to farmers are described as well as those involved in var. improvement. The adoption of new var. was found to modify farmers' preferences; for example, in the high plateau areas, short-cycle, bush-type var. were preferred over var. with type IV growth habit and longer growth cycle. Furthermore, artisan-scale seed production was considered a viable alternative to help solve production deficiencies, given the farmers' tendency to produce their own seed. (CIAT)